The effect of centella asiatica extract in Zebrafish (Danio rerio) larvae as a Chronic Constant Hypoxia (CCH) model - Ariani; Teni Widiyastuti (Medical Faculty of Brawijaya University, Indonesia, 2022)
Backgound: Chronic Constan Hypoxia (CCH) are able to occur in cyanotic congenital heart disease and bronchopulmonary dysplasia (BPD). Centella asiatica has antioxidant and neuroprotective effects in experimental animals.This study aims to observe the effect of Centella asiatica ethanol extract on Zebrafish in chronic hypoxic conditions Method: A laboratory experimental study with a randomized post-test controlled group design was conducted among 20 Zebrafish (Danio rerio) 3-8 day post fertilization (dpf) as samples per tube. The total group treatment was five with inclusion and exclusion criterias. Variables assessed in this study included Average body length, locomotor activity, and the relationship between average body length and locomotor activity. Data were analyzed using SPSS version 18 for Windows. Result: There was a moderate significant correlation between Centella asiatica concentration of 1.25 µg/ml, 2.5 µg/ml, 5 µg/ml with an enhancement of body length (r=0.431) and locomotor activity (r=0.262) in zebrafish larvae CCH model (p<0.05). Conclusion: It can be concluded that chronic constan hypoxia (CCH) inhibit the growth of body length and decrease locomotor activity in Zebrafish larvae. Centella asiatica treatment can avoid the CCH by using various concentration.